Sulfoxide as a Ligand in Iron(II) Porphyrinates: S– or O–Bound? - Hu, Chuanjiang (2007)
In order to study the bonding of sulfoxides to iron(II) porphyrinates, an equilibrium study of Fe(TPP) with tetramethylenesulfoxide (TMSO) has been performed. UV-vis spectra at different concentrations of TMSO have shown distinct character belonging to three species: four-coordinate Fe(II)(TPP), five-coordinate [Fe(II)(TPP)(TMSO)] and six-coordinate [Fe(II)(TPP)(TMSO)(2)]. The isosbestic points for the low TMSO concentrations suggest that the equilibrium constant K(1) is much larger than K(2). Analysis of spectral data by the nonlinear least-squares program SQUAD gives K(1) = 267 and K(2) ≈ 1. Even though the five-coordinate species is the dominant species under the synthetic conditions, only the six-coordinate species was crystallized and characterized by an X-ray diffraction study. [Fe(TPP)(TMSO)(2)] (C(52)H(44)Fe-N(4)O(2)S(2)): monoclinic, P2(1)/c, a = 11.2580(3) Å, b = 15.9262(5) Å, c = 12.3930(4) Å, β = 116.246(1)°, V = 1992.95(10) Å(3), Z = 2. X-ray crystallography demonstrates the complex is a low-spin bis-TMSO ligated species. The average Fe–N(p) distance is 1.999(4) Å. The most important feature is that TMSO is coordinated to iron(II) by the sulfur donors, not oxygen. The Fe–S distance is 2.2220(3) Å.